Review of: Kaposy C. (2018) Choosing Down Syndrome - Chevalier, Meghan (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2019)
With the advent of Non-Invasive Prenatal Testing, Chris Kaposy believes that more people should choose to parent children with Down Syndrome. Kaposy advocates for the Social Disability Model and recommends a normative pragmatic approach as standard. He makes use of both quantitative and qualitative evidence to support his position.